Exploring the Relationship Between Endogenous Pain Modulation, Pain Intensity, and Depression in Patients Using Opioids for Chronic Low Back Pain. Issue 10 (22nd October 2022) - Lazaridou, Asimina; Paschali, Myrella; Zgierska, Aleksandra E.; Garland, Eric L.; Edwards, Robert R.
Abstract : Introduction: Endogenous pain modulatory processes appear to play an important role in shaping pain-related outcomes, but we know relatively little about the influence of psychosocial factors on those pain modulatory processes. The primary objective of this study was to explore associations between endogenous pain modulation (ie, conditioned pain modulation, CPM; temporal summation, TS), chronic pain, and negative affective factors (ie, depression, anxiety symptoms) in a sample of participants with chronic low back pain (CLBP) treated with long-term daily opioids. Methods: Adults with opioid-treated CLBP (N=107) completed questionnaires assessing pain, pain symptoms, and psychological measures. CPM and TS were evaluated as predictors of pain intensity ratings (Brief Pain Inventory), with depression scores (Hospital Anxiety and Depression Scale, depression subscale) examined as potential moderators of those associations. Results: Moderation analyses demonstrated associations between CPM and back pain intensity ratings, moderated by depression symptom scores ( B =−0.002, SE=0.0008, P <0.01) when controlling for daily opioid dose, with participants with higher depression scores showing a relatively stronger link between lower CPM and increased pain intensity ratings. Significant associations were observed between depression, pain intensity, and CPM-derived outcomes. Conclusion: Our findings suggest that reduced pain-inhibitory capacity is associated with elevated self-reported pain intensity in adults with opioid-treated CLBP, particularly among those with higher severity of depression symptoms.